Research on English Translation of Shaanxi Folk Songs under the Perspective of Translation Aesthetics (Journal of Global Humanities and Social Sciences, 2023)
Shanbei folk song, an art form full of flavor and emotion, carries the deep historical and cultural heritage of the Shanbei region. It is not only a form of music, but also a kind of emotional communication, a kind of cultural communication. Songs are emotional bridges across cultures and languages, and through translation, the emotions and life experiences of the people of northern Shaanxi can be shared with people all over the world. By translating northern Shaanxi folk songs into English, more people can understand and appreciate this unique art form, thus better spreading traditional Chinese culture. However, when translators try to translate them into English, many difficulties and challenges follow, such as language barriers and cultural differences. Therefore, how to correctly deal with the challenges and accomplish high-quality translation is the key concern of every translator. Based on this, this paper elaborates on the specific path of English translation of Shaanxi folk songs from the perspective of translation aesthetics.